การศึกษาเปรียบเทียบหลักสูตรปริญญาโท สาขาวิชาดนตรีศึกษาของมหาวิทยาลัยในประเทศไทย - สุภนิธิ กัลย์ธีรา; พร้อมสุขกุล ปรีญานันท์ (Journal of Education Studies, Chulalongkorn University, 2018)
The purposes of this study were: 1) to compare the Master’s Degree curricula in music education offered in Thailand and 2) to study the identity of each selected Master’s Degree curricula in Music Education in Thailand. This qualitative study applies comparative research methodology to content analysis with Thailand Qualification Framework No.2. The results of the study showed that: 1) the purpose of each selected Master’s Degree curriculum in Music Education is similar to produce music teachers, lecturers, researchers and scholars. However, only 2 of 8 programs specify Music Education as a major – Chulalongkorn University and Buriram Rajabhat University – and there tends to be differences in curriculum structures; 2) the identity of each Master’s Degree curriculum varies in results from the curriculum structure and credit proportion which affects professional knowledge and the ability of graduates. This study provides useful comparative information for those interested in Music Education curriculum. Also, it can be used as a guideline to improve or develop the curriculum in music education in the future.